Sosialisasi Strategi Branding E-Commerce pada Pelaku UMKM di Kelurahan Manggar - Ismiyati, Nur; Jumriana, Jumriana; Rizki A, Andhika Ade; Prasetyo, Sukono Hadi; Prasetya, Audrey Putri; Farras, Muhammad Anwar; Rahman, Rezki Abdul; Pratama, Gery Andra Putra; Alim, Putra Chandra Rachmat; Haris, Muhammad Fadel; Amirullah, Amirullah; Yahya, Rony (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
University of Balikpapan continues to innovate in providing benefits to the community through the Real Work Lecture (KKN) program. Manggar Village KKN students carried out E-Commerce Branding Socialization activities as a better marketing and financial monitoring medium. This activity was attended by MSME actors in the local Manggar Village area which was held on August 25, 2024. This socialization activity aims to introduce and increase understanding of the use of digital technology, especially the E-Commerce system as a marketing tool for MSME actors. This activity method is carried out in 2 stages, namely the preparation stage and the implementation stage of the activity. Through digital marketing, MSMEs have wider opportunities to market products and a larger market reach. With this knowledge and skills, it is hoped that MSME actors can optimize market potential through digital marketing and are expected to be able to empower MSME actors to be able to compete in a better digital era. The results of this activity were that 85 MSME actors attended this activity and the enthusiasm of the participants to ask questions in this activity.